Proceedings of the International Conference on Social Modeling and Simulation, plus Econophysics Colloquium 2014 - Takayasu, Hideki; Ito, Nobuyasu; Noda, Itsuki; Takayasu, Misako (Springer Proceedings in Complexity, 2015)
Springer Proceedings in Complexity